PREPARING FUTURE TEACHERS FOR HEALTH-PRESERVING ACTIVITIES IN THE OUTBREAK OF EMERGENCIES (ResearchJet Journal of Analysis and Inventions, 2021)
The article deals with the problem of psychological, medical and pedagogical training of future teachers for health-preserving activities in the outbreak of an emergency. Information is provided on measures to provide urgent psychological and health-preserving assistance to victims at the time of a natural disaster and at the stage of rehabilitation after exposure to emergencies resulting from natural disasters.